Intramyocellular Lipid and Impaired Myofiber Contraction in Normal Weight and Obese Older Adults. (23rd September 2015) - Choi, Seung J.; Files, D. Clark; Zhang, Tan; Wang, Zhong-Min; Messi, Maria L.; Gregory, Heather; Stone, John; Lyles, Mary F.; Dhar, Sanjay; Marsh, Anthony P.; Nicklas, Barbara J.; Delbono, Osvaldo
Abstract : Background: Evidence implicates the amount and location of fat in aging-related loss of muscle function; however, whether intramyocellular lipids affect muscle contractile capacity is unknown. Methods: We compared both in vivo knee extensor muscle strength, power, and quality and in vitro mechanical properties of vastus lateralis single-muscle fibers between normal weight (NW) and obese older adults and determined the relationship between muscle lipid content (both intramuscular adipose tissue and intramyocellular lipids) and in vivo and in vitro muscle function in NW and obese individuals. Results: The obese group had a greater percentage of type-I fibers compared to the NW group. The cross-sectional area of type-I fibers was greater in obese compared to NW; however, maximal shortening velocity of type-I fibers in the obese was slower compared to NW. Type-I and type-IIa fibers from obese group produced lower specific force than that of type-I and type-IIa fibers from the NW group. Normalized power was also substantially lower (~50%) in type-I fibers from obese adults. The intramyocellular lipids data showed that total lipid droplet area, number of lipid droplets, and area fraction were about twofold greater in type-I fibers from the obese compared to the NW group. Interestingly, a significant inverse relationship between average number of lipid droplets and single-fiber unloaded shortening velocity, maximal velocity, and specific power was observed in obese participants. Additionally, muscle echointensity correlated with single-fiber specific force. Conclusions: These data indicate that greater intramyocellular lipids are associated with slower myofiber contraction, force, and power development in obese older adults.